2020
DOI: 10.2147/ott.s236543
|View full text |Cite
|
Sign up to set email alerts
|

<p>Transcriptomics Analysis of the Tumor-Inhibitory Pathways of 6-Thioguanine in MCF-7 Cells via Silencing DNMT1 Activity</p>

Abstract: Background: 6-thioguanine (6-TG), as a conventional "ancient" drug for the treatment of acute leukemia, has been proved to have extensive anti-tumor roles. This study was created to investigate the hidden function of 6-TG on the MCF-7 breast cancer cell line (ER+, PR+) and its mechanisms. Methods: MCF-7 cells were treated with 6-TG, and the IC50 value was measured by a cell counting kit-8 assay. Differentially expressed genes (DEGs) were confirmed by RNA-seq analysis. Apoptosis and cell cycle consequences were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Based on the online database of StarBase V2.0, the lncRNA-miRNA pairs were predicted and seven candidate lncRNAs and 125 miRNAs were compared. Both pathway enrichment and the results of a previous study (12) demonstrated that apoptosis and the p53 signaling pathway were the two main pathways induced by 6-TG in MCF-7 cells, and the aberrant expression of mRNAs from these two pathways is depicted in Table II. Next, the target miRNAs of these differentially expressed mRNAs were predicted using TargetScan, miRDB and miRTarBas online software.…”
Section: Matching Of Lncr Nas-mir Nas and Prediction Of Mrnas-mirna Imentioning
confidence: 73%
See 4 more Smart Citations
“…Based on the online database of StarBase V2.0, the lncRNA-miRNA pairs were predicted and seven candidate lncRNAs and 125 miRNAs were compared. Both pathway enrichment and the results of a previous study (12) demonstrated that apoptosis and the p53 signaling pathway were the two main pathways induced by 6-TG in MCF-7 cells, and the aberrant expression of mRNAs from these two pathways is depicted in Table II. Next, the target miRNAs of these differentially expressed mRNAs were predicted using TargetScan, miRDB and miRTarBas online software.…”
Section: Matching Of Lncr Nas-mir Nas and Prediction Of Mrnas-mirna Imentioning
confidence: 73%
“…Data processing and differential expression analysis. The sequencing data of samples from the MCF-7 control and 6-TG groups were obtained from a previous study (12). The raw data were available from the NCBI GEO database (https://www.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations